2015
DOI: 10.1007/s11255-015-1138-2
|View full text |Cite
|
Sign up to set email alerts
|

A simple, rapid, and efficient method for isolating detrusor for the culture of bladder smooth muscle cells

Abstract: Pure detrusor can be acquired from bladder wall conveniently using novel method. This novel method brought about significantly higher purity and cell livability as compared to traditional method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The merged image (Fig. 2H) was in accordance with our previous study 18 . Cell viability assay showed that almost all SMCs before harvest were live (Fig.…”
Section: Characterization Of Smc Sheetssupporting
confidence: 89%
“…The merged image (Fig. 2H) was in accordance with our previous study 18 . Cell viability assay showed that almost all SMCs before harvest were live (Fig.…”
Section: Characterization Of Smc Sheetssupporting
confidence: 89%
“…SMCs and EPCs were cultured as previously described 18 - 20 . Briefly, a pure detrusor strip approximately 10 × 5 mm was cut down from the bladder wall.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four rabbits were prepared as described for muscle biopsy 20 , 22 and randomly divided into 3 treatment groups with 8 animals each: 1) cell-sheet transplantation (sheet only group), 2) capsule flap (capsule only group), and 3) vascularized capsule prelaminated with smooth muscle cell sheets (sheet plus capsule group). In each group, the bladder neck (far from the biopsy site) was dissected under a surgical microscope and the muscular layer was separated from the urothelium, followed by a partial detrusorectomy with a mean diameter of 20.0 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Bladder SMCs were isolated as previously described[ 15 ]. Briefly, an approximately 10 × 5 mm smooth muscle strip was excised at vesical vertex and incised into segments.…”
Section: Methodsmentioning
confidence: 99%